The geography of the life-world – Spatialising the social theory of Alfred Schütz - Rotfuß, Eberhard; Dörfler, Thomas (ERDKUNDE, 2023)
The aim of this article is to highlight a frequently neglected aspect of Alfred Schütz’ social theory by suggesting a new spatial and bodily reading of his phenomenology. This change in emphasis should allow disciplines exploring the interrelations of the social and the spatial, especially human geography, to address a relative blind spot in the research by allowing a bodily perspective to be better incorporated methodologically in explanations of socio-spatial phenomena. To this end, the phenomenological social sciences - along with their hermeneutic-reconstructive methods – should be emphasised in their potential for contributing to contemporary discussions on the spatial turn. The voids of contemporary approaches are addressed as we also continue existing phenomenological work in human geography to deepen an understanding of the concept of the life-world (Lebenswelt) - especially of its spatial dimensions. This also enables us to make a proposal for the further development of our methodology, formulating a specific ‘Leib-based’ approach to the social and physical world.